CuBiSCl2 microparticle, preparation method thereof and solar cell
Patent Information
- Application Number
- CN202610817127.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-08
- Publication Date
- 2026-10-13
Smart Images

Figure CN122897437A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell and semiconductor optoelectronic materials technology, specifically to a CuBiSCl2 micron sheet and its liquid-phase thermal injection preparation method, as well as a solar cell based on the micron sheet. Background Technology
[0002] In recent years, halide perovskite materials have led to a rapid increase in battery efficiency due to their excellent defect tolerance. However, they contain the toxic element lead and are extremely sensitive to humidity and temperature, and their instability hinders their practical application. Therefore, the search for novel light-absorbing layer materials that are lead-free, stable, and defect-tolerant has become a research hotspot in the photovoltaic field.
[0003] Among numerous lead-free photovoltaic candidate systems, CuBiSCl2 is considered a highly promising light-absorbing layer material for solar cells due to its ideal bandgap, excellent chemical stability, and environmental friendliness. However, the synthesis of this type of multi-component compound currently relies heavily on traditional solid-state methods, which suffer from long reaction cycles and cumbersome processes. Furthermore, the resulting products are mostly large-sized bulk materials with poor processing performance, making it difficult to prepare high-quality photovoltaic thin films and limiting their application in practical devices. Summary of the Invention
[0004] In view of the above problems, this invention provides a solution-processable CuBiSCl2 microsheet, a method for preparing the same, and a sensitized solar cell containing the CuBiSCl2 microsheet material. This invention achieves, for the first time, the low-temperature and rapid synthesis of CuBiSCl2 microsheets using a solution method. Compared with traditional solid-state methods, the method of this invention is simpler, consumes less energy, has a shorter reaction cycle, and the product is solution-processable, thus enabling the large-scale preparation and application of this type of material.
[0005] In a first aspect, the present invention provides a CuBiSCl2 micron sheet. The CuBiSCl2 micron sheet has an orthorhombic crystal structure, a lateral dimension of 1-10 micrometers, and a thickness of 50-300 nanometers.
[0006] In an optional embodiment, the CuBiSCl2 microsheet has an optical band gap of 1.3 eV.
[0007] In a second aspect, the present invention provides a method for preparing CuBiSCl2 microsheets, comprising the following steps: (1) mixing a copper source, a bismuth source, an organic ligand, and a non-coordinating solvent, and heating the mixture to 100-150°C under an inert atmosphere for degassing to obtain a metal precursor solution; (2) dissolving a sulfur source and a chlorine source in an organic solvent to form a sulfur-chlorine mixed precursor solution; (3) injecting the sulfur-chlorine mixed precursor solution into the metal precursor solution at a reaction temperature of 130-250°C and maintaining the reaction for 10-150 min; (4) cooling, separating, and purifying the mixture after the reaction to obtain CuBiSCl2 microsheets.
[0008] In an optional embodiment, the molar ratio of chlorine in the chlorine source to bismuth in the bismuth source is 2:1 to 10:1; the molar ratio of sulfur in the sulfur source to bismuth in the bismuth source is 1:1; and the molar ratio of copper in the copper source to bismuth in the bismuth source is 1:1.
[0009] In an optional embodiment, the copper source is selected from at least one of cuprous salt and copper salt; the bismuth source is selected from at least one of organic acid bismuth salt, bismuth halide or inorganic acid bismuth salt; the sulfur source is selected from at least one of bis(trimethylsilyl)sulfide, elemental sulfur or thioamide compound; and the chlorine source is selected from at least one of acyl chloride compound or organochlorosilane.
[0010] In an optional embodiment, in step (1), the organic ligand is oleic acid, the non-coordination solvent is octadecene, and the degassing time is not less than 30 min; in step (3), the sulfur-chlorine mixed precursor solution is injected in a one-time rapid injection.
[0011] Thirdly, the present invention provides a solar cell based on CuBiSCl2 micron-sized sheets. The device structure of the solar cell includes a conductive substrate, a dense electron transport layer, a mesoporous electron transport layer, a photosensitive layer, an electrolyte layer, and a counter electrode arranged in sequence, wherein the photosensitive layer comprises the CuBiSCl2 micron-sized sheets.
[0012] In an optional embodiment, both the dense electron transport layer and the mesoporous electron transport layer are TiO2 layers; the electrolyte layer is a liquid electrolyte containing I⁻ / I3⁻ redox pairs; and the counter electrode is a platinum counter electrode.
[0013] In an optional embodiment, the photosensitive layer is prepared by immersing a substrate with a TiO2 layer deposited as a mesoporous electron transport layer in a CuBiSCl2 micron-sized sheet dispersion for adsorption, and then heat-treating it at 100~200℃.
[0014] In an optional embodiment, the open-circuit voltage of the solar cell under standard illumination conditions is 0.62 V, and the photoelectric conversion efficiency is not less than 0.9%.
[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention marks the first time that CuBiSCl2 micron-sized sheets have been synthesized at low temperature and rapidly using a solution method. Compared to traditional solid-state methods, this invention offers a simpler process, lower energy consumption, shorter reaction cycle, and solution-processable products, thus enabling the large-scale preparation and application of this type of material. Attached Figure Description
[0016] Figure 1 The XRD patterns of CuBiSCl2 prepared in Examples 1-6 are shown. Figure 2 SEM images of CuBiSCl2 prepared in Examples 1 and 4-5; Figure 3 The optical absorption spectrum (a) of CuBiSCl2 prepared in Example 1 and the band gap diagram determined by Tauc-Plot (b); Figure 4 Thermal stability (a) and temperature and humidity stability (b) of CuBiSCl2 prepared in Example 1; Figure 5 A schematic diagram (a) and current-voltage curve (b) of the solar cell based on CuBiSCl2 as the sensitization layer prepared in Example 1. Figure 6 The XRD patterns of CuBiSCl2 prepared in Examples 5 and 7-8 are shown. Figure 7 The XRD patterns of CuBiSCl2 prepared in comparative examples 1-5 are shown. Detailed Implementation
[0017] The present invention is further illustrated below through examples. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the invention.
[0018] The CuBiSCl2 microsheets provided by this invention have an orthorhombic crystal structure, exhibiting a two-dimensional irregular sheet shape, and possess good crystallinity and phase purity. In an optional embodiment, the lateral dimensions of the CuBiSCl2 microsheets are 1-10 micrometers, and the thickness is 50-300 nanometers. The band gap (optical band gap) of the CuBiSCl2 microsheets can reach 1.30 eV. Furthermore, the CuBiSCl2 microsheets exhibit excellent thermal stability at 260°C. In addition, this material composition is lead-free, and its stability to temperature and humidity is significantly superior to existing halide perovskite photovoltaic materials.
[0019] This invention also provides a method for preparing CuBiSCl2 microsheets. The method employs a hot injection method and includes the following steps: (1) mixing a copper source, a bismuth source, an organic ligand, and a non-coordinating solvent, and heating the mixture to 100-150°C under an inert atmosphere for degassing to form a metal precursor solution; (2) injecting a mixed solution of a sulfur source and a chlorine source (in an organic solvent) into the metal precursor solution at a reaction temperature of 130-250°C, and reacting for 10-150 min; (3) cooling the mixture after the reaction is completed, and obtaining the CuBiSCl2 microsheets through purification.
[0020] The above injection process can be achieved using a syringe. For example, after preparing the sulfur-chlorine mixed precursor solution in a glove box, the solution is drawn up using a syringe, then quickly transferred to a fume hood and rapidly injected into a three-necked flask containing the metal precursor solution. The injection time can be 3-5 seconds.
[0021] The injection is carried out under conditions that isolate water and oxygen. Alternatively, the metal precursor solution can be injected into a sulfur-chlorine mixed precursor solution, but in this process, it must be ensured that the metal precursor solution is a homogeneous solution and is isolated from water and oxygen.
[0022] This invention proposes for the first time a liquid-phase thermal injection method for the high-purity synthesis of CuBiSCl2 microsheets. Simply mixing copper, bismuth, sulfur, chlorine, and organic ligands in an organic solvent and then reacting under heating conditions cannot yield high-purity CuBiSCl2 microsheets. This is because the competitive growth between the multi-component components cannot be avoided, resulting in a large number of secondary competing phases in the reaction system. This leads to severely insufficient purity of the product phase, or even complete failure to obtain the target phase.
[0023] In an optional embodiment, the crystal growth of the micron-sized sheet is controlled by temperature. The preferred reaction temperature is 130-200°C. If the reaction temperature is too low or the reaction time is too short, the reaction driving force will be insufficient, the reaction will be incomplete, resulting in incomplete conversion of the precursor, making it difficult to generate the target product, or the appearance of impurity phases. If the reaction temperature is too high or the reaction time is too long, the product will decompose, and impurity phases will appear.
[0024] The molar ratio of chlorine in the chlorine source to bismuth in the bismuth source is 2:1 to 10:1, preferably 2:1 to 5:1, and more preferably 3:1. This ratio can maintain pure phase formation and avoid raw material waste caused by excessive feeding.
[0025] The molar ratio of sulfur in the sulfur source to bismuth in the bismuth source is 1:1.
[0026] The molar ratio of copper in the copper source to bismuth in the bismuth source is 1:1.
[0027] The copper source is selected from at least one of cuprous salts and copper salts, including but not limited to cuprous acetate, copper acetate, copper nitrate, copper chloride, and copper acetylacetyl. The bismuth source is selected from at least one of organic bismuth acid salts, bismuth halides, or inorganic bismuth acid salts, including but not limited to bismuth acetate, bismuth chloride, bismuth nitrate, and bismuth thiocarbamate. The sulfur source is selected from at least one of bis(trimethylsilyl)sulfide (also known as hexamethyldisilyl sulfide), elemental sulfur, or thioamide compounds, including but not limited to hexamethyldisilyl sulfide and dodecanethiol. The chlorine source is selected from at least one of acyl chloride compounds or organochlorosilanes, including but not limited to benzoyl chloride. The organic ligand is oleic acid. The organic ligand is used to induce the growth of CuBiSCl2 crystals along a specific crystal orientation to form a two-dimensional sheet-like structure. In an optional embodiment, the molar ratio of copper source to oleic acid is 1:(10~20). In an optional embodiment, the molar ratio of copper source to octadecene is 1:(10~20).
[0028] The noncoordination solvent is octadecene.
[0029] In an optional implementation, the degassing time is not less than 30 minutes.
[0030] In an optional implementation, the sulfur-chlorine precursor solution is injected in a single, rapid injection.
[0031] In optional embodiments, the organic solvents used to dissolve the sulfur and chlorine sources are not limited, including but not limited to noncoordinate solvents, such as octadecene.
[0032] The present invention also provides a sensitized solar cell, which uses the CuBiSCl2 micron sheet described in the present invention as the sensitization layer.
[0033] The solar cell includes, in sequence, a conductive substrate, a dense electron transport layer, a mesoporous electron transport layer, a sensitization layer formed by loading the CuBiSCl2 microsheet, an electrolyte layer, and a counter electrode. In an optional embodiment, the solar cell based on the CuBiSCl2 microsheet has a device structure that, from bottom to top, includes: a conductive substrate, a dense electron transport layer, a mesoporous electron transport layer, a photosensitive layer, an electrolyte layer, and a counter electrode.
[0034] The photosensitive layer comprises the CuBiSCl2 microsheets. For example, the photosensitive layer is prepared by immersing a substrate with a deposited mesoporous TiO2 layer in a CuBiSCl2 microsheet dispersion for adsorption, followed by heat treatment at 100-200°C (e.g., 100-150°C). In other words, the sensitized layer is formed on the surface of mesoporous TiO2 through an immersion adsorption process and then heat-treated at 100-200°C. The counter electrode is a platinum electrode deposited on FTO.
[0035] In an optional embodiment, the solar cell comprises, in sequence, a conductive substrate, a dense electron transport layer, a mesoporous electron transport layer, a sensitization layer formed by loading the CuBiSCl2 micron sheet, an electrolyte layer, a counter electrode, and a conductive substrate.
[0036] As an example, the conductive substrate is FTO glass, both the dense electron transport layer and the mesoporous electron transport layer are TiO2 layers, and the photosensitive layer is prepared by immersing the substrate with the mesoporous TiO2 layer in a CuBiSCl2 micron-sized sheet dispersion for adsorption, and then heat-treating it at 100~200℃ for 10~30 min; the electrolyte layer is a liquid electrolyte containing I⁻ / I3⁻ redox pairs; and the counter electrode is a platinum counter electrode.
[0037] After testing, the solar cell achieved a measured open-circuit voltage of over 0.60 V under standard illumination, and its photoelectric conversion efficiency was close to 1%. For example, under standard illumination, the solar cell had an open-circuit voltage of 0.62 V and a photoelectric conversion efficiency of no less than 0.9%.
[0038] The following is an exemplary description of the synthesis of the CuBiSCl2 microsheet and the battery fabrication process.
[0039] The raw materials required for synthesizing CuBiSCl2 micron-sized sheets include a copper source, a bismuth source, a sulfur source, and a chlorine source. The preferred copper source is cuprous acetate, the preferred bismuth source is bismuth acetate, the preferred sulfur source is hexamethyldisilazane sulfide, and the preferred chlorine source is benzoyl chloride. The reaction is carried out in a system containing an organic ligand (such as oleic acid) and a non-coordinate solvent (such as octadecene). According to the present invention, the size and crystallinity of the micron-sized sheets can be controlled by adjusting the reaction temperature.
[0040] The specific synthesis steps for CuBiSCl2 microsheets include: (1) Precursor preparation and degassing: copper source, bismuth source, oleic acid and octadecene are mixed and degassed at 100~150℃ by vacuum pumping and nitrogen circulation to remove moisture and oxygen from the system and obtain a transparent metal precursor solution.
[0041] (2) Thermal injection and growth: The system is heated to 130~250℃ and a mixed solution containing sulfur source and chlorine source is rapidly injected under inert gas protection. After injection, the reaction temperature is maintained for crystal growth, and the reaction time is 10~150 min.
[0042] (3) Purification treatment: After the reaction is completed, the mixture is cooled naturally and an antisolvent (such as acetone) is added to precipitate the product. The product is then obtained by centrifugation, washing and redispersing. High-purity CuBiSCl2 micron sheets are finally obtained.
[0043] Preparation of the sensitized layer: Purified CuBiSCl2 microsheets were redispersed in toluene to form a stable suspension. The FTO / dense TiO2 layer / mesoporous TiO2 layer substrate was immersed in the suspension using an immersion adsorption method, thus loading the microsheets onto the mesoporous TiO2. After removal, the substrate was annealed at 100–150 °C for 10–30 min to remove the organic solvent. The dense TiO2 layer was prepared by spin-coating a TiO2 precursor solution followed by annealing. The mesoporous TiO2 layer was obtained by blade coating a TiO2 slurry.
[0044] Solar cell assembly: Liquid electrolyte (containing I3 / I) is dropped onto the photoanode supported on the CuBiSCl2 micron-sized sheet. - The electrolyte of the redox couple is used to form a sandwich structure solar cell, which is then encapsulated with a platinum counter electrode.
[0045] In summary, this invention achieves high-purity synthesis of CuBiSCl2 microsheets via a liquid-phase thermal injection method. CuBiSCl2, as a lead-free quaternary sulfur halide semiconductor, possesses an ideal band gap of 1.30 eV. The CuBiSCl2 microsheets described in this invention exhibit good thermal stability at 260℃ and are completely lead-free, making them environmentally friendly. Due to the liquid-phase synthesis method, this material can be stably dispersed in organic solvents such as toluene, exhibiting good solution processability and enabling preparation at relatively low temperatures of 130–200℃. The synthesis route employed in this invention allows for precise control of the two-dimensional microsheet size, showing significant application potential in the field of solar cells.
[0046] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below.
[0047] Example 1
[0048] A liquid-phase synthesis method for CuBiSCl2 microsheets with two-dimensional sheet morphology and its application in solar cells.
[0049] Synthesis of CuBiSCl2 microsheets: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, followed by 6 mL of oleic acid and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120 °C for 30 min. Subsequently, the system was heated to 200 °C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisilazane sulfide and 4 mmol of benzoyl chloride was injected in one step. The reaction was maintained at 200 °C for 150 min.
[0050] FTO conductive glass substrates are commercially available substrates.
[0051] The preparation process of the dense TiO2 layer is as follows: First, solution A (containing 3 mL tetraisopropyl titanate, 34 mL ethanol, and 2.1 mL acetylacetone) is mixed with solution B (34 mL ethanol, 0.39 mL concentrated hydrochloric acid with a mass fraction of 36%~38%, and 1.7 mL deionized water). After stirring, the mixture is allowed to stand for two days to obtain an orange-yellow titanium dioxide precursor solution. This solution is then spin-coated onto FTO at 3000 rpm for 20 s. After spin-coating, the sample is annealed on a 100℃ hot plate for 10 min, and then transferred to a muffle furnace for sintering at 510℃ for 30 min to obtain a dense TiO2 thin layer.
[0052] The preparation process of the mesoporous TiO2 layer is as follows: 0.2 g of nano-TiO2 (P25) was added to 1 mL of terpineol and ball-milled in a ball mill jar for 4 h to obtain a uniform and stable TiO2 slurry. Then, an appropriate amount of the TiO2 slurry was coated onto an FTO / dense TiO2 substrate and annealed at 100℃ to remove the organic solvent. The sample was then placed in a muffle furnace for high-temperature annealing, slowly heated from room temperature to 510℃ for 30 min, and then naturally cooled to room temperature to obtain a mesoporous TiO2 film, thus obtaining the FTO / dense TiO2 layer / mesoporous TiO2 layer substrate.
[0053] Preparation of the sensitized layer: Purified CuBiSCl2 microsheets were redispersed in toluene to form a stable suspension. The FTO / dense TiO2 layer / mesoporous TiO2 layer substrate was immersed in the suspension using an immersion adsorption method, thus loading the microsheets onto the mesoporous TiO2. After removal, the substrate was annealed at 130℃ for 20 min to remove the organic solvent.
[0054] The electrolyte preparation process is as follows: The electrolyte is prepared using a mixed solvent of acetonitrile and valerate (volume ratio 85:15). Its composition is: 1,3-dimethylimidazolium iodide (1 M), lithium iodide (50 mM), iodine (30 mM), 4-tert-butylpyridine (0.5 M), and guanidine thiocyanate (0.1 M).
[0055] The platinum counter electrode was prepared by spin coating. A 20 mg / mL solution of chloroplatinic acid (H₂PtCl₆) was prepared using isopropanol as the solvent. This solution was spin-coated onto FTO conductive glass at 1500 rpm for 10 s. Subsequently, the sample was annealed at 100°C for 10 min to remove the organic solvent. Finally, the sample was transferred to a hot plate at 450°C and annealed for 30 min to obtain a uniformly loaded platinum counter electrode.
[0056] Assembly of the sensitized solar cell. The device has a sandwich structure, consisting of an FTO / dense TiO2 / mesoporous TiO2 / CuBiSCl2 photoanode, a platinum counter electrode, and a liquid electrolyte sandwiched between them. During assembly, an insulating tape is first used as a spacer layer. The conductive surfaces of the photoanode and counter electrode are placed opposite each other with a certain distance maintained, and then fixed in place by applying uniform pressure with clamps. A small hole is left at the edge of the tape for subsequent electrolyte injection. The final effective area of the encapsulated cell is 0.09 cm². 2 .
[0057] Example 2
[0058] The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets was as follows: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, followed by 6 mL of oleic acid and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120°C for 30 min. The system was then heated to 250°C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisiloxane and 4 mmol of benzoyl chloride was injected in one step. The reaction was maintained at 250°C for 150 min.
[0059] Example 3
[0060] The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets was as follows: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, followed by 6 mL of oleic acid and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120°C for 30 min. The system was then heated to 180°C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisilazane sulfide and 4 mmol of benzoyl chloride was injected in a single injection. The reaction was maintained at 180°C for 150 min.
[0061] Example 4
[0062] The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets was as follows: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, followed by 6 mL of oleic acid and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120°C for 30 min. The system was then heated to 150°C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisiloxane and 4 mmol of benzoyl chloride was injected in one step. The reaction was maintained at 150°C for 150 min.
[0063] Example 5
[0064] The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets was as follows: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, followed by 6 mL of oleic acid and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120°C for 30 min. The system was then heated to 130°C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisilazane sulfide and 4 mmol of benzoyl chloride was injected in one step. The reaction was maintained at 130°C for 150 min.
[0065] Example 6
[0066] The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets was as follows: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, followed by 6 mL of oleic acid and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120°C for 30 min. The system was then heated to 100°C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisilazane sulfide and 4 mmol of benzoyl chloride was injected in one step. The reaction was maintained at 100°C for 150 min.
[0067] See Figure 1 X-ray diffraction patterns showed that all diffraction peaks of the product matched the standard CuBiSCl2 pattern, proving that high-purity products could be obtained within a wide process window of 130–200 °C. At 250 °C, the sample began to decompose due to the longer reaction time and was difficult to stabilize. At 100 °C, a BiOCl impurity phase was obtained.
[0068] See Figure 2 SEM images show that the product exhibits a clear, irregular two-dimensional microplate morphology, with a lateral size distribution ranging from 1 to 10 micrometers and a thickness ranging from 50 to 300 nanometers. The size of the CuBiSCl2 microplates decreases with increasing temperature.
[0069] See Figure 3 The absorption spectra of the microsheet were measured using a UV-Vis diffuse reflectance spectrometer, and then fitted using Tauc-Plot. The band gap of the microsheet was approximately 1.30 eV, exhibiting good light absorption characteristics.
[0070] See Figure 4 The thermal stability was tested under the following conditions: temperature range of room temperature to 500℃, heating rate of 10℃ / min, under a N2 atmosphere, and the weight change was observed. The results showed that the CuBiSCl2 micron-sized sheet material did not undergo thermal decomposition at medium to high temperatures (below 260℃). The humidity stability was tested by storing the sample in a constant temperature (27℃), constant humidity (60% humidity), and air environment for 14 days, and observing the changes in the XRD pattern. The results showed that the XRD pattern of the CuBiSCl2 micron-sized sheet material did not change significantly, demonstrating its good stability.
[0071] See Figure 5 The solar cell was assembled according to the device structure, and then the current-voltage curve was tested (test conditions: AM 1.5G, 100 mW / cm). 2 The results show that the short-circuit current and open-circuit voltage of the solar cell using CuBiSCl2 as the sensitizer are 2.31 mA / cm². 2 At a voltage of 0.62 V, the photoelectric conversion efficiency is 0.97%. This provides an important foundation for the practical application and further research of CuBiSCl2 semiconductor material as a light-absorbing layer.
[0072] Example 7
[0073] The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets was as follows: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, followed by 6 mL of oleic acid and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120°C for 30 min. The system was then heated to 130°C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisilazane sulfide and 4 mmol of benzoyl chloride was injected in one step. The reaction was maintained at 130°C for 10 min.
[0074] Example 8
[0075] The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets was as follows: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, followed by 6 mL of oleic acid and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120°C for 30 min. The system was then heated to 130°C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisilazane sulfide and 4 mmol of benzoyl chloride was injected in one step. The reaction was maintained at 130°C for 60 min.
[0076] See Figure 6The results showed that when the reaction time was 10 min, the reaction was not complete, and only a small number of CuBiSCl2 diffraction peaks appeared, accompanied by a large number of impurity peaks. After the reaction time was extended to 1 h, the characteristic diffraction peaks of CuBiSCl2 increased significantly, but a small number of impurity peaks still existed. When the reaction time was further increased to 2.5 h, CuBiSCl2 with higher purity could be obtained, and its XRD pattern was in good agreement with the calculated results.
[0077] Comparative Example 1 The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets involved adding 1 mmol of cuprous acetate and 1 mmol of bismuth acetate to a three-necked flask, along with a mixture of oleylamine and oleic acid (volume ratio 1:3, total volume 6 mL) and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120 °C for 30 min. The system was then heated to 130 °C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisiloxane and 4 mmol of benzoyl chloride was injected in a single injection. The reaction was maintained at 130 °C for 150 min.
[0078] Comparative Example 2 The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets involved adding 1 mmol of cuprous acetate and 1 mmol of bismuth acetate to a three-necked flask, along with a mixture of oleylamine and oleic acid (volume ratio 2:3, total volume 6 mL) and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120 °C for 30 min. The system was then heated to 130 °C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisiloxane and 4 mmol of benzoyl chloride was injected in a single injection. The reaction was maintained at 130 °C for 150 min.
[0079] Comparative Example 3 The process was essentially the same as in Example 1, except for the following: The synthesis of CuBiSCl2 microsheets involved adding 1 mmol of cuprous acetate and 1 mmol of bismuth acetate to a three-necked flask, along with a mixture of oleylamine and oleic acid (volume ratio 3:3, total volume 6 mL) and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120 °C for 30 min. The system was then heated to 130 °C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisiloxane and 4 mmol of benzoyl chloride was injected in a single injection. The reaction was maintained at 130 °C for 150 min.
[0080] See Figure 7 The XRD results of comparative examples 1-3 did not show the CuBiSCl2 phase, but only the BiOCl impurity phase, indicating that the addition of oleylamine was not conducive to the reaction.
[0081] Comparative Example 4 The process was essentially the same as Comparative Example 1, with the only difference being the synthesis of CuBiSCl2 microsheets: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, along with a mixture of oleic acid and oleylamine (volume ratio 3:3, total volume 6 mL) and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120 °C for 30 min. Subsequently, the system was heated to 150 °C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisiloxane and 4 mmol of benzoyl chloride was injected in one go. The reaction was maintained at 150 °C for 150 min.
[0082] See Figure 7 The XRD of this comparative example did not show the CuBiSCl2 phase, but only the Cu3BiS3 impurity phase was found, indicating that the addition of oleylamine is not conducive to the reaction.
[0083] Comparative Example 5 The process was essentially the same as Comparative Example 1, with the only difference being the synthesis of CuBiSCl2 microsheets: 1 mmol of cuprous acetate and 1 mmol of bismuth acetate were added to a three-necked flask, along with a mixture of oleic acid and oleylamine (volume ratio 3:3, total volume 6 mL) and 4 mL of octadecene. The mixture was continuously stirred and degassed at 120 °C for 30 min. Subsequently, the system was heated to 200 °C, and a 1 mL solution of octadecene containing 1 mmol of hexamethyldisiloxane and 4 mmol of benzoyl chloride was injected in one go. The reaction was maintained at 200 °C for 150 min.
[0084] See Figure 7 The XRD of this comparative example did not show the CuBiSCl2 phase, but only the Cu3Bi2S4Cl impurity phase was found, indicating that the addition of oleylamine is not conducive to the reaction.
[0085] The above description is only a preferred embodiment of the present invention regarding the synthesis of CuBiSCl2. Any non-essential improvements made by those skilled in the art based on this description should be included within the scope of protection of the present invention.
Claims
1. A CuBiSCl2 micron-sized sheet, characterized in that, The CuBiSCl2 microsheets have an orthorhombic crystal structure, with a lateral dimension of 1-10 micrometers and a thickness of 50-300 nanometers.
2. The CuBiSCl2 micron sheet according to claim 1, characterized in that, The optical band gap of the CuBiSCl2 micron sheet is 1.3 eV.
3. A method for preparing CuBiSCl2 micron-sized sheets according to claim 1 or 2, characterized in that, The process includes the following steps: (1) mixing a copper source, a bismuth source, an organic ligand, and a non-coordinating solvent, and heating the mixture to 100-150°C under an inert atmosphere for degassing to obtain a metal precursor solution; (2) dissolving a sulfur source and a chlorine source in an organic solvent to form a sulfur-chlorine mixed precursor solution; (3) injecting the sulfur-chlorine mixed precursor solution into the metal precursor solution at a reaction temperature of 130-250°C and maintaining the reaction for 10-150 min; (4) cooling, separating, and purifying the mixture after the reaction to obtain CuBiSCl2 microsheets.
4. The preparation method according to claim 3, characterized in that, The molar ratio of chlorine in the chlorine source to bismuth in the bismuth source is 2:1 to 10:1; the molar ratio of sulfur in the sulfur source to bismuth in the bismuth source is 1:1; and the molar ratio of copper in the copper source to bismuth in the bismuth source is 1:
1.
5. The preparation method according to claim 3 or 4, characterized in that, The copper source is selected from at least one of cuprous salts and copper salts; the bismuth source is selected from at least one of organic acid bismuth salts, bismuth halides or inorganic acid bismuth salts; the sulfur source is selected from at least one of bis(trimethylsilyl)sulfide, elemental sulfur or thioamide compounds; and the chlorine source is selected from at least one of acyl chloride compounds or organochlorosilanes.
6. The preparation method according to any one of claims 3 to 5, characterized in that, In step (1), the organic ligand is oleic acid, the non-coordination solvent is octadecene, and the degassing time is not less than 30 min; in step (3), the sulfur-chlorine mixed precursor solution is injected in a one-time rapid injection.
7. A solar cell based on CuBiSCl2 micron-sized sheets, characterized in that, The device structure of the solar cell includes a conductive substrate, a dense electron transport layer, a mesoporous electron transport layer, a photosensitive layer, an electrolyte layer, and a counter electrode arranged in sequence, wherein the photosensitive layer comprises CuBiSCl2 microsheets according to claim 1 or 2.
8. The solar cell according to claim 7, characterized in that, Both the dense electron transport layer and the mesoporous electron transport layer are TiO2 layers; the electrolyte layer is a liquid electrolyte containing I⁻ / I3⁻ redox pairs; and the counter electrode is a platinum counter electrode.
9. The solar cell according to claim 7 or 8, characterized in that, The photosensitive layer is prepared by immersing a substrate with a TiO2 layer deposited as a mesoporous electron transport layer in a CuBiSCl2 micron-sized sheet dispersion for adsorption, and then heat-treating it at 100~200℃.
10. The solar cell according to any one of claims 7 to 9, characterized in that, The open-circuit voltage of the solar cell under standard illumination conditions is 0.62 V, and the photoelectric conversion efficiency is not less than 0.9%.